Learning Communities for Teaching Practice School Placements: A Higher Education Initiative to Promote Equity for Students with Disabilities (Journal of Student Affairs in Africa, 2021)
In South Africa, scholarship on the teaching practice learning experiences for students with disabilities is a relatively new area of sociological inquiry. Social justice arrangements in the South African Higher Education policy frameworks identify the equity imperative as being of critical importance for social redress and transformation for all students. This qualitative study drew on the teaching practice school placement experiences of five Bachelor of Education students with either visual or physical disabilities and who were part of a teaching practice learning community. The findings of this study suggest that, for students with visual and physical disabilities, learning communities were perceived to be a structure that enhanced equity arrangements for human development and well-being in teaching practice school placements. In addition, and in alignment with equity arrangements, the need for a social justice reform agenda for teaching practice school placements emerged from the data. The study concludes that learning communities as a context-specific institutional structure support freedom, agency, dialogue and participation, and respect for disability required for capability expansion for human development and well-being in the teaching practice school placements of students with visual and physical disabilities. These were found to enhance equity arrangements for students with visual disabilities and physical disabilities.
Keywords: equity; learning community; physical disabilities; teaching practice school placements; visual disabilities